Pemasaran Produk Pendidikan - Suyarti, Sri; Suhendi, Andreas; Kumagaya, Yohanes (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
Marketing of educational products is a key element in increasing the attractiveness and success of educational institutions in a competitive market. This study aims to explore effective marketing strategies for various educational products, including educational programs, tutoring services, learning materials, and educational facilities. This study uses qualitative methods to identify and analyze best practices in marketing educational products through literature studies and data analysis from academic sources. This research method is a literature study with a qualitative approach. This research method uses a qualitative approach to gain an in-depth understanding of marketing educational products. Data were collected through in-depth interviews with various stakeholders, including educational product managers, customers, and marketing experts. The results of the study indicate that effective marketing strategies for educational products involve several key elements. Proper market segmentation helps in understanding the target group and tailoring marketing strategies to their needs. Product differentiation, by highlighting competitive advantages, such as unique curricula and superior facilities, is also an important factor. Digital marketing, including the use of websites and social media, and reputation management through testimonials and reviews, has been shown to increase visibility and attract prospective students. These findings provide insight into how an integrated marketing strategy can increase the attractiveness and success of educational institutions